2019
DOI: 10.1111/jocn.15074
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate students' perspectives on pursuing a career in mental health nursing following practicum experience

Abstract: Aims and objectives The purpose of this study was to explore how undergraduate students perceive and make decisions regarding mental health nursing as a career following completion of an inpatient mental health practicum. Background Among nursing students, mental health is consistently perceived as the least desirable nursing career path. However, evidence to explain why this is the case remains limited, with a lack of research exploring students' experiences of mental health settings and how these experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…This attitudinal change is consistent with prior literature on the importance of positive placements in respect to students’ choice to pursue a career in the field (Happell & Gaskin 2013; Slemon et al . 2020). It does need to be acknowledged however, as Happell and Gaskin (2013) found, this will not necessarily translate into increased numbers of graduates entering the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This attitudinal change is consistent with prior literature on the importance of positive placements in respect to students’ choice to pursue a career in the field (Happell & Gaskin 2013; Slemon et al . 2020). It does need to be acknowledged however, as Happell and Gaskin (2013) found, this will not necessarily translate into increased numbers of graduates entering the field.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Canada, Slemon et al . (2020) found that on mental health inpatient placement students enjoyed engaging with consumers and developing therapeutic relationships. However, they also described non‐therapeutic and unsafe staff practices which they did not want to adopt in their own practice, and which negatively affected their interest in pursuing a career in acute mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudantes afastam-se da especialidade por não perceberem as competências necessárias para o trabalho de Enfermagem em saúde mental. Hildegard Peplau afirmava que conhecer e compreender a profissão e o seu fazer é um pressuposto para o cuidado do outro e consequente emancipação (40)(41) .…”
Section: O Cuidado De Enfermagem Em Saúde Mental é Um Direito De Todosunclassified
“…), stigmatization, previous clinical practice in the psychiatric nursing area, and perceptions of theoretical preparedness were found to affect the understanding of nursing care 22 . Other factors that influence students' career decisions are the qualities of theoretical and clinical education, the institutional environment of the psychiatric clinics, behavior health‐care professionals, perceptions of working with a psychiatric patient, perspectives toward mental health care, and perceptions of psychiatric nursing 20,23–25 . In a study conducted with master's entry nursing students, students found psychiatry nursing practice valuable.…”
Section: Introductionmentioning
confidence: 99%